Mortality, Enzymatic Antioxidant Activity and Gene Expression of Cabbage Aphid (Brevicoryne brassicae L.) in Response to Trichoderma longibrachiatum T6 - Inayat, Rehan; Khurshid, Aroosa; Boamah, Solomon; Zhang, Shuwu; Xu, Bingliang (Frontiers in Physiology, 2022)
Aphids are one of the most common insect pests in greenhouse and field crops worldwide, causing significant crop yields and economic losses. The objective of this study was to determine the mortality, enzymatic antioxidant activity and gene expression of cabbage aphids (Brevicoryne brassicae L.) in response to Trichoderma longibrachiatum T6 (T6) at different time points from Day 1 to 7 after inoculation. Our results showed that the highest mortality of B. brassicae was observed on Day 7 at a concentration of 1×108 spores/ml (73.3%) after inoculation with T6 compared with the control on Day 7 (11.5%). The activities of the enzymes superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT), ascorbate peroxidase (APX), glutathione peroxidase (GPX) and glutathione S-transferase (GST) were increased by 52.98%, 44.77%, 48.26%, 49.48%, 45.13% and 39.67%, respectively, on day 3 after inoculation with T6 compared to the control. Howerver increased days post treatment (dpt) decreased the activites of SOD, POD, CAT, APX, GPX and GST enzymes by 20.79%, 21.05%, 13.75%, 20.45%, 25.38%, and 19.76% repectively on Day 7 compared to control. The transcript levels of SOD, POD, CAT, GPX, and GST genes were increased by 11.89, 10.87, 13.79, 7.32, and 5.00-fold respectively at Day 3 after inoculation with T6 in comparison to the control. However, the SOD, POD, CAT, GPX, and GST transcription levels decreased by 0.65, 0.57, 0.66, 0.58 and 0.53-fold respectively, compared to control at Day 7. Our results suggest that the T6 strain has a potential effect on the mortality, antioxidant activity and its genes expression of B. brassicae, and therefore could be used as a natural biocontrol agent against B. brassicae in the future.